Museum practices and the posthumanities - Cameron, Fiona, 1960- author.
1 online resource.
Keywords: "This book critiques modern museologies and curatorial practices, which are dominated by the thoughts and practices of modern humanism in which capital growth, social, technological advancement, hubris, extraction, speciest logics and colonial domination predominate, often without reflection. While history, science and technology museums and their engagement with the non-human world have always been ecological as an empirical reality, the human subject-based object frameworks and forms of human agency that institutions deploy tend to be non-cognizant of this reality. Museum Practices and the Posthumanities reveals how these practices are ill-equipped to deal with radical transformations in society, including rapid digital technological changes, the challenges of the Covid pandemic in a post-Covid world, climate change and its impacts, and impending socio-ecological collapse. The book presents novel, more-than-human curatorial visions, methods, conceptual frameworks, policies, and museologies as part of a radical refiguration of the epistemological foundations of curatorial and museological thinking and practice. This book is aimed towards museological scholars and museum professionals, and it will provide them with the inspiration to conduct research on and curate from a different ecological reference point to promote a world good enough for all things to live and thrive in radical co-existence"--